2006
DOI: 10.1021/cm060157b
|View full text |Cite
|
Sign up to set email alerts
|

Triazole Cycloaddition as a General Route for Functionalization of Au Nanoparticles

Abstract: Triazole formation by 1,3-dipolar cycloaddition reactions, “click” chemistry, has been used to functionalize the surfaces of Au nanoparticles. Au particle samples were first synthesized through standard procedures, the methyl-terminated chains partially exchanged with ω-bromo-functionalized thiol, and the Br termini converted to azides by reaction with NaN3. These particles were then reacted with a series of alkynyl derivatized small molecules in nonpolar solutions, which led to their attachment through the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(150 citation statements)
references
References 55 publications
6
135
1
3
Order By: Relevance
“…76,147 Examples of species that have been coupled to surfaces in this way include, oligo(ethylene oxides) to render surfaces protein resistant, 151 peptides, 152 DNA strands, 153 carbohydrates, 154 porphyrins 155 and quinones. 156 Of these many studies, one by our group illustrates an additional advantage of this class of chemistry. We modified hydrogen terminated Si(100) surfaces with an a,o-dialkyne (1,8-nonadiyne) via a hydrosilylation reaction.…”
Section: ''Click'' Reactions Between Azides and Alkynesmentioning
confidence: 99%
“…76,147 Examples of species that have been coupled to surfaces in this way include, oligo(ethylene oxides) to render surfaces protein resistant, 151 peptides, 152 DNA strands, 153 carbohydrates, 154 porphyrins 155 and quinones. 156 Of these many studies, one by our group illustrates an additional advantage of this class of chemistry. We modified hydrogen terminated Si(100) surfaces with an a,o-dialkyne (1,8-nonadiyne) via a hydrosilylation reaction.…”
Section: ''Click'' Reactions Between Azides and Alkynesmentioning
confidence: 99%
“…Gel electrophoresis verified that several lipases had covalently attached to each nanoparticle, without any nonspecific binding, and a lipase assay showed that they still retained their enzymatic activity. Following a similar procedure, Fleming et al (87) were able to conjugate several different alkynyl derivatives, including ferrocene, aniline, and PEG, to gold nanoparticles via the click reaction.…”
Section: Gold and Magnetic Nanoparticlesmentioning
confidence: 99%
“…A new vibration band at approximately 2100 cm ¹1 is detected that is attributed to the antisymmetric stretching vibration of the cumulated double bond of the terminal azido groups. 25) As previously described, methylene-spacered samples tend to adsorb higher amounts of nitrogen during nitrogen sorption, have larger pore diameters (D BHJ,Des ) and slightly higher specific surface areas (S BET ) compared to the propyl-spacered samples. 15) The structural parameters for azido-modified silica gels obtained after exposure to DMF/NaN 3 for 2 d at different temperatures are exemplarily given in Table 1 (a complete overview of the structural parameters of azidoalkyl-modified samples synthesized with different exposure temperatures and times are listed in Table 1/ESI).…”
Section: Resultsmentioning
confidence: 78%